Comparison of Open Cholecystectomy versus Laparoscopic Cholecystectomy in Treatment of Gallstone Diseases - Wangtrakulchai, Suradaj (Journal of Health Science of Thailand, 2017)
Year by year an increasing incidence of gallstone diseases resulting in a large number of admissions has been observed. The objective of this descriptive, retrospective study was to compare outcomes of open cholecystectomy with laparoscopic cholecystectomy. Data were collected from medical records and hospital bills of 109 gallstone diseases patients in Nakornping hospital during October 1, 2005 - September 30, 2006. Those with gallstone, common duct stone, or combined gallstone and common duct stone and undergoing either laparoscopic cholecystectomy (LC) or open cholecystectomy (OC) were included in this case control study design at 0.05 level of significance. Data analysis to confirm differences between three groups of the patients were t-test and Fisherีs exact test, and odds ratio were used to estimate the differences of operative complications and amount of pethidine used between the two operation methods. The study showed that postoperative pain in LC was reportedly less than that of OC. However, OC showed better outcomes regarding less operative complications and lower hospital expenses. In addition, LC had some advantage over OC in diagnosis of comorbidity in kidney stone in some patients yet it was more costly.